Blood-based biomarkers of age-associated epigenetic changes in human islets associate with insulin secretion and diabetes - Karl Bacos (Nature Portfolio, 2016)
Aging is associated with impaired pancreatic islet function, increased risk of type 2 diabetes, and changes in DNA methylation. Here the authors find blood-based biomarkers that reflect age-associated DNA methylation changes in human pancreatic islets associated with insulin secretion and diabetes.